O processo de implementação da política pública do trabalho do adolescente aprendiz em Cuiabá/MT a égide da Lei 10.097/2000 - Silva, Sara Cíntia Ferreira da (2012)
This study aims to analyze with proposals of how social policy advocated by Law 10.097/2000 has been implemented in Cuiabá – MT, along the period from 2009 to 2011, compared to its limits and possibilities, from the perspectives of different social subjects involved: teenage apprentices representatives of qualifying entities who join the program, responsible for the process of learning the practical part and standard-setters and supervisory bodies of that matter. The theoretical profile methodology adopted is based on the critical dialectical method with the use of technical-operative instrumentals, bibliographical study, observation and semi-structured interviews conducted with 13 adolescents apprentices, 8 guardian / guiding the company which runs the practical learning, 6 coordinators from nongovernmental entities, 1 coordinator from the “S” system, and two representatives of the supervisory board: the Guardianship Council and the Regional Labor. The theoretical discussion part of the core categories, labor and adolescence, understanding that, in general, work appears as a form of participation in social life, which should be reserved for adults. However, this does not happen: the economic structure highly unequal in terms of income distribution, associated with the growth of the juvenile population, mostly originated of the excluded social layers, led it to a dramatic increase in the number of teenage workers to ensure their own subsistence. Therefore, it is in fact the capitalist system which includes the Law 10.097/2000, characterized as milestone for dealing with such issues as public policy focused on teenage segment. The data collected in the survey showed that public policy has involved and included many cuiabanos adolescents into the labor market through the notifications that the Regional Labor has performed in these companies. After 12 years of its implementation, the work of adolescent apprentices continue to run improperly and seen as cheap labor. It can be said that the implementation of Law is occurring slowly, especially by agencies responsible for implementation and monitoring of actions aimed at training of teenagers as apprentices.